ASSESSMENT OF THE FIRE RESISTANCE OF BUILDINGS FROM FIREPROOF REINFORCED CONCRETE BUILDING STRUCTURES - Maiboroda, R.; Otrosh, Yu.; Rashkevich, N.; Melezhyk, R. (Municipal economy of cities. Series: «Economy science», 2023)
The authors conducted an analysis of the current state of evacuation of low-mobility population groups from high-rise residential buildings in the event of a fire. The analysis of the literature made it possible to formulate a number of obstacles to the effective evacuation of people from high-rise residential buildings. Norms in the field of fire safety are not perfect and, as a rule, are aimed at ordinary categories of citizens. The goal of approaches to evacuation calculations is to reduce the time it takes to evacuate residents of a high-rise building in the event of a fire. The authors substantiated the possibility of safe self-evacuation in the event of a fire of the less mobile population groups using fire elevators. Mathematical and graphical calculations of people's evacuation time were carried out using the Pathfinder software complex with the use (without use) of fire elevators. The authors performed a mathematical calculation of the time of evacuation of people and the time of blocking by dangerous factors of fire evacuation routes during a fire in accordance with the methodology of DSTU 8828:2019 Fire safety. Terms. Kyiv: Technical Committee "Fire Safety and Fire Fighting Equipment". To confirm the effectiveness of using fire elevators for the evacuation of people belonging to the M4 population groups with limited mobility (disabled people who move around in wheelchairs), the calculation part was performed. The object of the calculations is a high-rise apartment building on the street. Baidy Vyshnevetskoho, 68 in Cherkasy. The authors determined the dependence of the evacuation time on the movement parameters of people of different mobility groups. The authors compared calculations of evacuation time by stairwell and using fire elevators. Fire elevators are effective when evacuating people from floors for the category of mobility group M4. The researchers proposed management solutions to increase the level of fire safety, ensure the constant readiness and operability of fire elevators for evacuating people with reduced mobility from high-rise residential buildings.